Hypotension prediction index decision support system: a new model for decision support in hemodynamic management - Valbuena-Bueno, Miguel A.; Ripollés-Melchor, Javier; Ruiz-Escobar, Alicia; Fernández-Valdes-Bango, Paula; Lorente, Juan V.; Abad-Gurumeta, Alfredo; Monge-García, M. Ignacio (Frontiers in Anesthesiology, 2024)
Intraoperative hypotension (IOH) poses significant risks during surgeries, necessitating effective management to ensure patient safety and successful outcomes. The Hypotension Prediction Index (HPI) software was developed as a decision support model to assist anesthesiologists in monitoring and addressing hypotensive episodes during non-cardiac surgeries. We have utilized the predictive capabilities of HPI and the physiological variables provided by the Hemosphere monitor to create a Decision Support System (HPI-DSS) for hemodynamic management. This article presents a comprehensive overview of the HPI-DSS, detailing its model for hemodynamic decision support. The system's performance and its ability to enhance intraoperative management are discussed. The article explores the methodology, results, and limitations of the HPI-DSS. It also covers potential applications of the system and offers suggestions for further research to improve and refine its capabilities.